S11 Expression of Tenascin-C Regulates Airway Smooth Muscle Derived Matrix Metalloproteinase-1 in Asthma. (19th November 2012) - Rogers, NK; Clements, D; Harrison, TW; Shaw, D; Johnson, SR
Abstract : Background: Collagenases are differentially regulated in conditions of lung remodelling. Literature documents the capacity of extracellular matrix (ECM) proteins to induce collagenase expression. The current study aims to characterise ECM regulation of the collagenase matrix metalloproteinase-1 (MMP-1) in human airway smooth muscle (ASM) cells, and the applicability of this mechanism to remodelling. Methods: ASM cells were derived from patients with and without asthma and cultured with ECM proteins for 24 hours. MMP-1 gene expression was quantitated by Real-time PCR, with secreted protein and activity levels assessed by ELISA, Western Blotting and fluorometric activity assay. Pathways mediating MMP-1 induction were mapped using a phosphoprotein array, specific inhibitors and blocking antibodies. Tenascin-C and MMP-1 expression were studied in endobronchial biopsies from patients with and without asthma by immunohistochemistry. Results: Tenascin–C increased MMP-1 mRNA, protein and activity in a dose and time dependent manner. Tenascin-C phosphorylated MAPK intermediates ERK and P38, and inhibitors to these intermediates attenuated MMP-1 induction. Blocking antibodies showed this response was mediated by the β1 and β3 integrins. Control tissue showed minimal tenascin-C and MMP-1 expression, but strong co-localising Tenascin-C and MMP-1 expression in the subepithelial layer and to a lesser extent in ASM bundles. ASM cells from patients with asthma had elevated basal levels of MMP-1, which was further increased by Tenascin-C stimulation. Discussion: Tenascin-C upregulates expression and activity of MMP-1 via the β1 and β3 integrin subunits and MAPK signalling in ASM cells. These proteins were increased in lung remodelling diseases, with overlapping localisation. The functional consequences of this observation needs to be evaluated in vivo, however, this could potentially yield a new target for therapeutic in airway remodelling.